“Instant Tradition”—A Challenge to Legal Education in the Twenty-First Century - Richard B. Kuhns (Washington University Law Quarterly, 1998)
Anheuser-Busch Hall, the new home of Washington University School of Law, is a huge squarish structure that creates an imposing presence at the northwest corner of the hilltop campus. The facade of pink granite and limestone attempts to mimic the collegiate Gothic style of other campus buildings, and the interior with its abundance of dark wood doors, beams, tables, and carrels is suggestive of the Inns of Court. All in all, the building, at least upon first impression, seems to stand as a monument to the tradition and stability of the law. Indeed, a Washington University press release describes the structure as "majestic." In a number of respects, however, Anheuser-Busch Hall is at best only a superficial symbol of these values. More importantly, in their zeal to symbolize the tradition and stability of the law, the planners and architects of Anheuser-Busch Hall looked backward rather than forward. As a result, they ignored values that should receive symbolic recognition in any building designed to educate lawyers for the twenty-first century. Part I of this essay provides a critique of Anheuser-Busch Hall as a symbol of tradition and stability. Part II discusses how Anheuser-Busch Hall ignores or undermines values that should be critical to the education of lawyers in the twenty-first century. Finally, Part III contains some modest suggestions, and offers reason to hope that a better established and more forward-looking tradition of the law school will prove to be more enduring than the "instant tradition" of Anheuser-Busch Hall.
Keywords: Architecture -- Law & legislation; Law schools -- Missouri; Legal education; Washington University. School of Law